Parent–adolescent communication on sexual and reproductive health issues and associated factors among secondary public-school students in Gondar town, northwest Ethiopia: an institution based cross-sectional study - Melese, Mihret; Esubalew, Dereje; Siyoum, Tsehayu Melak; Worku, Yilkal Belete; Azanaw, Jember; Mengistie, Berihun Agegn (Frontiers in Public Health, 2024)
Introduction Effective communication between adolescents and their parents is crucial for reducing sexual health problems. This open dialogue can help address misconceptions, provide accurate information, and foster a supportive environment where adolescents feel comfortable seeking guidance and discussing sensitive issues related to their sexual health. In Ethiopia, with its diverse ethnic and cultural background, effective communication between parents and adolescents about sexual and reproductive health (SRH) is crucial in reducing the likelihood of adolescents engaging in risky sexual behaviors. Despite the importance of such communications, there were no data showing the level of parent–adolescent communication (PAC) in secondary public schools in Gondar town. Therefore, this study aimed to determine the level of parent–adolescent communication on sexual and reproductive health issues along with its influencing factors, among secondary students in Gondar town, northwest Ethiopia. Methods We employed an institution-based cross-sectional study design. A total of 424 students were recruited using a systematic random sampling technique, with a 100% response rate. We developed a structured questionnaire from the related literature to collect data from the participants of the study. The data were entered using EpiData version 4.6, and analyzed using SPSS version 25. A binary logistic regression model was fitted to identify associated factors. Results The proportion of adolescents who had communicated with their parents was 37.7% (95% CI: 34.65–44.76). In a multivariable analysis at a 95% confidence interval (CI), variables such as being female (adjusted odds ratio (AOR) = 2.23; 95% CI: 1.09–7.45), belonging to grades 11–12 (AOR = 1.25; 95% CI: 1.19–6.98), living with parents/caregivers (AOR = 1.26; 95% CI: 1.07–5.66), having a positive attitude toward sexual health (AOR = 2.4; 95% CI: 1.34–7.82), having poor knowledge about SRH issues (AOR = 1.23; 95% CI: 1.04–7.81), and having good knowledge about the puberty period (AOR=1.23; 95% CI:1.04–7.89) were statistically associated with parent–adolescent communication. Conclusion and recommendations This study found a low level of communication between parents and adolescents regarding sexual and reproductive health (SRH) issues. To address this challenge, it is crucial to implement evidence-based education on SRH topics, such as consent, healthy relationships, communication skills, STDs, contraception, and interpersonal dynamics. Enhancing parent–adolescent dialogue on SRH can be achieved by implementing peer education among senior students and training teachers in effective communication techniques. The study also recommended conducting qualitative research to explore the specific barriers affecting parent–adolescent communication.